Perception of direct vs. averted gaze in portrait paintings: An fMRI and eye-tracking study - Kesner, Ladislav; Grygarová, Dominika; Fajnerová, Iveta; Lukavský, Jiří; Nekovářová, Tereza; Tintěra, Jaroslav; Zaytseva, Yuliya; Horáček, Jiří (Brain and cognition, 2018)
In this study, we use separate eye-tracking measurements and functional magnetic resonance imaging to investigate the neuronal and behavioral response to painted portraits with direct versus averted gaze. We further explored modulatory effects of several painting characteristics (premodern vs modern period, influence of style and pictorial context). In the fMRI experiment, we show that the direct versus averted gaze elicited increased activation in lingual and inferior occipital and the fusiform face area, as well as in several areas involved in attentional and social cognitive processes, especially the theory of mind: angular gyrus/temporo-parietal junction, inferior frontal gyrus and dorsolateral prefrontal cortex. The additional eye-tracking experiment showed that participants spent more time viewing the portrait's eyes and mouth when the portrait's gaze was directed towards the observer. These results suggest that static and, in some cases, highly stylized depictions of human beings in artistic portraits elicit brain activation commensurate with the experience of being observed by a watchful intelligent being. They thus involve observers in implicit inferences of the painted subject's mental states and emotions. We further confirm the substantial influence of representational medium on brain activity.
Keywords: Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; pohyby očí; Humans; Perception; lidé středního věku; mapování mozku; Attention; oční fixace; Eye Movements; Emotions; Female; malířství; dospělí; mladý dospělý; Direct gaze; lidé; Paintings; fMRI; Averted gaze; Brain Mapping; sociální percepce; Adult; ženské pohlaví; Male; Middle Aged; Brain; Fixation, Ocular; emoce; Young Adult; Eye-tracking; mužské pohlaví; Social Perception; Artistic portraits; pozornost